First Language Use in Second and Foreign Language Learning - Dailey-O'Cain, Jennifer; Turnbull, Miles (Second Language Acquisition, 2009)
This volume offers fresh perspectives on a controversial issue in applied linguistics and language teaching by focusing on the use of the first language in communicative or immersion-type classrooms. It includes new work by both new and established scholars in educational scholarship, second language acquisition, and sociolinguistics, as well as in a variety of languages, countries, and educational contexts. Through its focus at the intersection of theory, practice, curriculum and policy, the book demands a reconceptualization of code-switching as something that both proficient and aspiring bilinguals do naturally, and as a practice that is inherently linked with bilingual code-switching